Adolescent environmental tobacco smoke exposure predicts academic achievement test failure. - Collins, B; Wileyto, E; Murphy, M; Munafò, MR (2007)
PURPOSE: Research has linked prenatal tobacco exposure to neurocognitive and behavioral problems that can disrupt learning and school performance in childhood. Less is known about its effects on academic achievement in adolescence when controlling for known confounding factors (e.g., environmental tobacco smoke [ETS]). We hypothesized that prenatal tobacco exposure would decrease the likelihood of passing academic achievement tests taken at 16 and 18 years of age. METHODS: This study was a longitudinal analysis of birth cohort data including 6,380 pregnant women and offspring from the 1958 National Child Development Study (NCDS). Academic pass/fail performance was measured on British standardized achievement tests ("Ordinary Level" [O-Level] and Advanced Level: [A-Level]). Prenatal tobacco exposure plus controlling variables (ETS, teen offspring smoking and gender, maternal age at pregnancy, maternal smoking before pregnancy, and socioeconomic status) were included in regression models predicting O- and A-Level test failure. RESULTS: Significant predictors of test failure in the O-Level model included exposure to maternal (OR = 0.71, p < .0001) and paternal (OR = 0.70, p < .0001) ETS, as well as teen smoking, female gender, and lower SES. Prenatal tobacco exposure did not influence failure. Similar factors emerged in the A-Level model except that male gender contributed to likelihood of failure. Prenatal exposure remained nonsignificant. CONCLUSIONS: Our model suggests that adolescent exposure to ETS, not prenatal tobacco exposure, predicted failure on both O- and A-Level achievement tests when controlling for other factors known to influence achievement. Although this study has limitations, results bolster growing evidence of academic-related ETS consequences in adolescence.